Islamic Educational Management for Seventh Grade Students at SMPN 1 Wonosegoro - Arif Budi Wibowo; Budi Utomo (Humaniora, 2018)
This research explored the application of Islamic educational management for 7th graders at SMPN 1 Wonosegoro. The case study used interview, observation, and documentation to collect data which later were analyzed qualitatively. This school was chosen as the research setting because despite being a non-Islamic institution where religious and moral cultures were not commonly incorporated in the curriculum and school activities, it had several exceptional religious programs. It is found that their Islamic educational management is concerned to three major sub-areas namely; student orientation, curriculum, and extracurricular activities. These programs have been reviewed to have given significant impacts on their moral, social, and religious values proven with the very low number of student delinquency and a very good record of prayer habits among students.